An innovative tool to assess the functional resilience of a school system: learning from the COVID-19 pandemic - Kaim, Arielle; Siman-Tov, Maya; Adini, Bruria; Lev-ari, Shahar (Frontiers in Psychology, 2023)
Preparing the school system for a future crisis requires the ability to examine the effectiveness of schools' functioning during distant learning and their level of preparedness for future crises. Functional resilience (FR) is defined as the ability to maintain vital operational continuity in the face of disturbance. The study objectives included to develop a FR index of schools and to evaluate and validate it. To enable examination of the study objectives, the study design included tool development, followed by a validation process among 20 content experts. Concurrently, an eDelphi process for building an inclusive index, based on various components of resilience was conducted. The final study tool consists of four tailored questionnaires to examine perceptions of key stakeholders, i.e.-teachers, principals, parents, and highschool students regarding communication, psychosocial aspects, perceived stress, infrastructure, resources, pedagogic support, digital literacy, and perceived FR. Using an internet panel, the tool was disseminated cross-sectionally among the four groups of stakeholders. The results showed high reliability of most of the scales developed. Furthermore, a high consensus level was reached on the relative importance of each component/ stakeholder to the schools FR. The findings further suggest that there were no significant differences in the composite FR score based on characteristics such as school type/ size/geographic location. However, the findings revealed interesting variations among stakeholders, with findings suggesting greater vulnerability among some. To increase resilience and preparedness for future adversities that school systems may face, it is recommended to periodically incorporate an assessment based on a structured tool.